2012
DOI: 10.1088/1748-3182/7/3/036003
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a bio-inspired lift-enhancing effector on a 2D airfoil

Abstract: A flap mounted on the upper surface of an airfoil, called a 'lift-enhancing effector', has been shown in wind tunnel tests to have a similar function to a bird's covert feathers, which rise off the wing's surface in response to separated flows. The effector, fabricated from a thin Mylar sheet, is allowed to rotate freely about its leading edge. The tests were performed in the NCSU subsonic wind tunnel at a chord Reynolds number of 4 × 10(5). The maximum lift coefficient with the effector was the same as that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…properly respond to flow separation (Johnston & Gopalarathnam 2012). Only the chord-wise section of the lower half of the airfoil (0.58 <= x/c <= 0.98) was therefore covered with flaps.…”
Section: Preparation Of the Airfoilmentioning
confidence: 99%
See 1 more Smart Citation
“…properly respond to flow separation (Johnston & Gopalarathnam 2012). Only the chord-wise section of the lower half of the airfoil (0.58 <= x/c <= 0.98) was therefore covered with flaps.…”
Section: Preparation Of the Airfoilmentioning
confidence: 99%
“…A comparison of the action of fixed and free-moving effectors has been drawn up by Johnston and Gopalarathnam (2012). The fixed-deployment effectors represented a useful means of studying the influence on the flow field and airfoil surface pressures while maintaining control over the deployment angle.…”
Section: Introductionmentioning
confidence: 99%
“…Venkataraman and Bottaro [23] performed a numerical study of the effect of hairy coatings on an NACA0012 aerofoil at low Reynolds number and high angle of attack , and found a set of coating parameters able to deliver an increase in lift (). Finally, the effectiveness of fixed versus free-moving flaps has been studied by Johnston and Gopalarathnam [9]. They found that also fixed flaps deliver an improvement in both lift and drag at high angles of attack.…”
Section: Introductionmentioning
confidence: 99%
“…The flap was found to produce a 7% increase in coefficient of lift (C L ) at stall (12,15) . In the years since 1997, many researchers have advanced our understanding of the pop-up flap in many areas including: optimisation of flap size and position (12,14,(16)(17)(18) , optimisation of flap material and geometry (9,17,19) , flap deployment angle (10,(19)(20)(21)(22) , flap performance at low Reynolds Number (Re) (11) , using pop-up flaps for drag reduction (23) , dynamic testing with the pop-up flap (24) , testing of pop-up flaps on highly elliptical low AR wings (25) , kinematics and stability of the wing and flap (26)(27)(28) , the effects of having multiple flaps (18) , and how hairy surfaces can have a similar function to the pop-up flap (8,29) .…”
Section: Background Information -High-lift Effectorsmentioning
confidence: 99%
“…The of 1,300-1,800 MPa, according to the manufacturer's technical data sheet). The flap size and position were based on published experimental results for a rigid wing (11,20,21) . To avoid the flap from being mechanically bound by the coupling of its stiffness and the spanwise deflection of the membrane on which the flap is hinged, the flap was cut along its spanwise direction into five sections free to rotate about their hinge.…”
Section: Test Articlementioning
confidence: 99%